Responsive Harmony in the Zhuangzi - Luyao Li (Religions)
This paper adopts a post-comparative approach to explore the concept of harmony in the Zhuangzi, moving beyond traditional comparative frameworks. It examines how Zhuangzian harmony offers a solution to the potential risks of domination that harmony may pose to individual freedom. It first challenges Chenyang Li’s distinction between Confucian “active harmony” (主动和谐) and Daoist “passive harmony” (被动和谐), arguing that the “passive” label fails to capture the characteristic of Zhuangzian harmony. Instead, Zhuangzian harmony is better understood as “responsive harmony” (随动和谐), a unique form of harmony that is neither passive nor merely the opposite of Confucian active harmony. Responsive harmony shares similarities with active harmony, yet it offers distinct features that address certain challenges to harmony, such as the risk of domination, which Confucian harmony may not fully resolve. This perspective provides a fresh philosophical resource from Daoism for addressing contemporary concerns about harmony in ethical contexts.